The Relationship Between Unemployment and Economic Growth in Selected Large Emerging Countries: A Revisit Using Threshold Regression Analysis - Mustafa Şit (İktisat Politikası Araştırmaları Dergisi)
This study aims to estimate the minimum rate of economic growth required to reduce unemployment in the large emerging markets economies of the Fragile Five (i.e., Brazil, India, Russia, South Africa, and Türkiye). As proposed by Hansen (1999), the study conducts a panel threshold analysis based on Okun’s law to determine threshold effects. This paper presents new evidence regarding Okun’s law over the past three decades for five large emerging markets. The findings suggest the relationship between the cyclical components of unemployment and GDP growth to be characterized by non-linearities. In particular, unemployment will fall if economic growth exceeds an average threshold of 5.5%. This result proves the validity of Okun’s Law regarding the threshold for the country group under investigation. This study has also proven that economic growth must exceed a certain level in order to reduce the unemployment rate in these economies. Policymakers in the Fragile Five should consider a minumum of 5.50% as an economic growth target to provide employment. When considering the unstable economic performance of the Fragile Five’s economies, structural reforms should be made to ensure adequate economic growth and increase employment. To address the problem of poor growth, this study can propose economic measures such as reducing employment taxes, producing investment and employment-based policies, and increasing the effectiveness of private employment offices.